THE SUCCESS OF ETHNICALLY BASED POLITICAL PARTIES: CASE OF SRI LANKA - Wijegoonawardana, Nirmali (International Journal of Research -GRANTHAALAYAH, 2020)
Ethnic identities or policy interests; what influences the Sri Lankan voter the most? This analysis will be done providing particular attention to the case of Sri Lanka. The development in electoral outcomes in Sri Lanka provides an explicitly clear image of how, particular political parties obtain support from particular ethnic groups and in return serve the interest of particular groups. This study will be based on the results of the 1989 Parliamentary General Election and 2010 Parliamentary General Election samples, mainly in the North and East constituencies. The Sri Lankan ethnic conflict offers an overview of the role of political parties and political actors in the competitive electoral system in relation to a conflicting situation. Therefore, this paper will examine as to how, such parties obtain support from particular ethnic groups and thereby safeguard the interest of those groups. Furthermore, this paper will seek to analyze how the, obtaining of moderate support from another ethnic group provides the best outcome but it is insufficient to divert from the interest of the group who provides the greatest support. Hence, this paper attempts at deciphering the main factor as to why it is harder for an ethnic party once established to become multi-ethnic.